Analysis of the territorial conflict between the Republic of Guyana and the Bolivarian Republic of Venezuela - Medina Rivas Plata, Anthony (2024)
This article examines the protracted territorial conflict between Venezuela and Guyana over the Essequibo region from a perspective of historical analysis. The scope of the study encompasses from the early attempts at peaceful conflict resolution in the late 19th century to contemporary challenges arising from the discovery of vast reserves of oil and gas in the disputed area; culminating with the April 2023 order from the International Court of Justice in The Hague directing Venezuela not to alter the status quo in the area until it issues a final judgment, which could take years. Through a comprehensive analysis of primary and secondary sources, it investigates how the claims of both nations have impacted bilateral relations and regional security. International mediation efforts are examined, including the roles played by the United Nations and the International Court of Justice in addressing the conflict and facilitating a lasting resolution. The research method includes reviewing official documents, diplomatic reports, contemporary news, and academic analyses, with a focus on critical and contextual interpretation of historical and contemporary events. The geopolitical and economic implications of the territorial dispute are discussed, as well as future prospects for conflict resolution. Ultimately, it is argued that the resolution of the conflict between Venezuela and Guyana has significant implications for regional stability and international cooperation in Latin America and the Caribbean.